USING OF DIFFERENT NOZZLES (SINGLE AND DOUBLE )UNDER TWO PRESSURES TO SHOW THERE EFFECT ON COEFFICIENT OF UNIFORMITY AND DISTRIBUTION UNIFORMITY OF WATER DISTRIBUTION UNDER STATIONARY SPRINGULAR IRRIGATION - Essam A. Taha (Mesopotamia Journal of Agriculture)
This study was conducted in the fields of Agriculture and forestry collage in February 2010 to investigate the effect of pressure 1.5 and 3 bar and type of nozzle single ( square , hexagon , circular ) and double ( square × circular , hexagon × circular , circular × circular ) on the uniformity coefficient of water distribution ( UC ) and distribution uniformity ( DU ) . The randomized block design and Duncan's multiple range test for comparison between the means were used . Results showed that there were significant differences among the two factor , the presser 3 bar gave the highest coefficient of water distribution uniformity and distribution uniformity the circular single nozzle gave the highest coefficient and distribution uniformity at pressure 1.5 , 3 bar comparing with the other nozzle , The double nozzle (circular × circular ) gave the highest coefficient and distribution uniformity at pressure 3 bar .